DELLA-NAC Interactions Mediate GA Signaling to Promote Secondary Cell Wall Formation in Cotton Stem - Wang, Yi; Yu, Wanting; Ran, Lingfang; Chen, Zhong; Wang, Chuannan; Dou, Yang; Qin, Yuanyuan; Suo, Qingwei; Li, Yaohua; Zeng, Jianyan; Liang, Aimin; Dai, Yonglu; et al. (Frontiers in Plant Science, 2021)
Gibberellin promotes secondary cell wall (SCW) development in plants, but the underlying molecular mechanism is still to be elucidated. Here, we employed a new system, the first internode of cotton, and virus-induced gene silencing (VIGS) method to address this problem. We found that knocking down the major DELLA genes via VIGS phenocopied GA treatment and significantly enhanced the SCW formation in the xylem and phloem of cotton stems. Cotton DELLA proteins were found to interact with a wide range of SCW-related NAC proteins, and VIGS of these NAC genes inhibited SCW development with down-regulated biosynthesis and deposition of lignin and cellulose. Our findings indicated a framework for GA’s regulation of SCW formation, that is, the interactions between DELLA and NAC proteins mediated the GA signaling to regulate SCW formation in cotton stems.